Fluorescent π‐Conjugated Polymer Dots versus Self‐Assembled Small‐Molecule Nanoparticles: What's the Difference?. Issue 33 (10th July 2013) - Fischer, Irén; Kaeser, Adrien; Peters‐Gumbs, Mauraline A. M.; Schenning, Albertus P. H. J.
Abstract Fluorescent nanoparticles based on π‐conjugated small molecules and polymers are two different classes of π‐conjugated systems that have attracted much interest. To date, both emerging classes have only been studied separately and showed no clear differences in their properties. Herein these nanoparticles are compared on the basis of a fluorene co‐polymer and its corresponding small molecule. Both systems formed nanoparticles with the same diameter, whereas the fluorescence properties clearly differed. In case of the polymer the fluorescence diminished, whereas for the small molecules the fluorescence increased. In addition, the capability of encapsulation and release of a hydrophobic dye from the fluorescent nanoparticles was studied. For the polymer system, encapsulation was highly efficient and no release was observed, whereas for the small molecule system encapsulation was less efficient and release of the dye was observed. These studies show a clear difference between small molecules and polymers which has important implications for the design of fluorescent nanoparticles.